Modulation of myocardial creatine transporter levels and the effects of gene regulation and post-translational modification on its function - Sebag-Montefiore, L (2012)
Heart failure (HF) is a common, disabling and deadly condition that causes high rates of morbidity and mortality worldwide. It is widely recognised that the failing heart is energy-starved, and that restoring energy homeostasis is a promising approach towards improving cardiac output. This thesis aims to address the role of energetics in the failing heart, by focussing on modulation of the creatine transporter (CrT). Creatine (Cr), together with the phosphocreatine shuttle, plays a vital role in maintaining energy supplies via ATP in times of high energy demand. Key to the regulation of intracellular [Cr] is the CrT, a Na+ and Cl- - dependent membrane transporter. Previous CrT genetic mouse models include a knockout model, found to still express cardiac CrT, and a cardiac-specific CrT overexpressing (OE) model with large variations in myocardial [Cr] between animals and Cr levels high enough to cause spontaneous hypertrophy. To overcome the shortfalls of this CrT-OE model, a novel in vivo model of temporal inducible expression of CrT is described, using a cardiac-specific tetracycline inducible (Tet-On) system. Ten transgenic lines (RCT) were created with a construct containing the CrT-HA (CrT cDNA with an haemagglutinin epitope tag), following successful doxycyline-inducibility in vitro. Eight lines showed germline transmission, with LV CrT OE achieved in an individual mouse that displayed double LV [Cr] compared to WT. Issues with the inducer line (rtTA) were ruled out by its use in the creation of a luciferase overexpressing mouse line; all mice tested demonstrated LV luciferase expression in response to doxycycline feeding. The failure to overexpress CrT could be attributed to position or copy number dependent suppression, or to position effect variegation in the case of the single OE mouse obtained. Subsequent work focussed on regulatory pathways in vitro in a cell line of mouse fibroblasts stably overexpressing CrT-HA. Post-translational modifications (PTMs) had been previously suggested to regulate CrT activity. Two N-linked glycosylation sites exist, in addition to the putative phosphorylation sites. Inhibition of glycosylation by tunicamycin led to decreased CrT activity, reflected by decreased Cr uptake capacity. Strategies to confirm the presence of phosphorylation were employed, including isolation of CrT-HA by immunoprecipitation and subsequent LC-MS / MS analysis to identify PTMs. Although the presence of CrT was confirmed in 5 different sized species- one previously unreported- inadequate sequence coverage prevented identification of any PTM sites. Tyrosine phosphorylation was not detected using a phosphospecific antibody on immunopurified CrT-HA. Candidate signalling pathways in vitro were then investigated to elucidate CrT regulation, namely the IGF 1R signalling pathway. This study included a cardiomyocyte-like mouse cell line (HL-1) in addition to 3T3-CrT-HA. Exposure of cells to extracellular insulin, growth hormone and IGF-1 led to increased Cr uptake of 125% - 300% of normal. Pharmacological inhibition of the downstream kinases PKA and PKC reduced the effect of insulin and GH, while PMA, sapintoxin (STX) and Gö 6976 induced CrT activity. The mammalian target of rapamycin (mTOR) is also a candidate regulator of CrT, as incubation with rapamycin decreased Cr uptake in 3T3-CrT-HA. Finally, a targeted approach on transcription factors in the 5'UTR region of mouse CrT identified HEY1 as a highly conserved site. In siRNA experiments, HEY1 was found to exert a mild effect on CrT activity, suggesting that regulation at the transcriptional level merits further investigation. Together, this work has provided novel insights into the modulation of CrT in vitro, identifying molecular and pharmacological targets in a known therapeutic signalling pathway. Further work could potentially develop these findings by identifying candidate compounds that would increase CrT activity, potentially in a tissue-specific manner.